El rol del lenguaje en la construcción del sujeto, una reflexión teórica - Sola-Morales, Salomé (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This essay intends to continue the reflection on language, focusing on its ontological and mediator status. The proposed thesis is that language is fundamental in all processes of construction of identities and in the formation of the self, the us and the them. Assuming the contributions of the linguistic turn as an epistemological option, it is revealed that the classical currents of language (formalism and structuralism) undermine their ability to transform everyday reality as well as subjects and groups. In this sense, a multifaceted, dialectic and mediator perspective is proposed, thanks to which it will be possible to understand the scope of the language in identity processes.